The Wasathiyyah Political Movements of Nahdlatul Ulama and Muhammadiyah in North Sumatra Post-1998 Reform Era - Jailani, Muhammad; Katimin, Katimin; Warjio, Warjio; Harahap, Elly Warnisyah; Adenan, Adenan (Fakultas Dakwah Institut Agama Islam Sunan Giri Ponorogo, 2024)
The rise of religious-based organizations, especially Islam after the 1998 reformation, led to a contestation between radical and moderate (wasathiyyah) streams. Organizations within the wasathiyyah group also experienced conflict. This study is an exploration of the wasathiyyah political movement carried out by Nahdlatul Ulama and Muhammadiyah in North Sumatra to explore the ontology of the wasathiyyah political movement of the organization, the construction of the movement, and the practice of the wasathiyyah political movement of NU and Muhammadiyah. This comparative qualitative study found that 1) Muhammadiyah's Wasathiyyah is based on the thoughts of KH. Ahmad Dahlan in 7 philosophies of life which are summarized into the nature of religion, renewal-purification (tajdid), education, and social charity, the theological basis of Al-Ma'un and openness is central to the Muhammadiyah's approach, while Nahdlatul Ulama (NU) adopts the term Ahlussunnah Wal Jamaah, characterized by tawasut, I'tidal, tawa>zzun, and tasa>muh. The construction of NU's wasathiyyah political movement is rooted in moral and value-based principles, focusing on cultural politics and actively influencing electoral processes through non-formal organizational channels. On the other hand, Muhammadiyah places emphasis on cultural politics, modernizing education, health, and social work, alongside charitable efforts and tajdid to purify Islamic teachings in line with the Qur'an and Sunnah. In the context of North Sumatra, NU's wasathiyyah political movement actively engages in electoral politics and strives to enhance religious understanding internally and externally through educational and religious activities, while maintaining religious traditions based on the teachings of Islam Ahlussunnah wal Jamaah. Conversely, Muhammadiyah prioritizes the renewal and purification of Islamic teachings, with a focus on education, health, and charitable efforts for its members and externally.